Description of Security Work Training Planning in PT Andalan Mitra Prestasi Kota Padang - Resven Feres; Irmawita Irmawita; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2020)
PT. Andalan Mitra Prestasi company training provider in the field of security services aimed at the personal and corporate. Training is considered successful because of the many companies that are interested in the training. Data is collected using questionnaires, while data analysis techniques using percentage calculations. The results of this study indicate that (1) more than half of the participants are already making preparations for training (2) more than half of the participants have fulfilled planning priorities that follow the many activities during the training and evaluating practices directly.Keywords: Planning, Training, Education